2014
DOI: 10.3390/life4040666
|View full text |Cite
|
Sign up to set email alerts
|

Function and Regulation of Ferredoxins in the Cyanobacterium, Synechocystis PCC6803: Recent Advances

Abstract: Ferredoxins (Fed), occurring in most organisms, are small proteins that use their iron-sulfur cluster to distribute electrons to various metabolic pathways, likely including hydrogen production. Here, we summarize the current knowledge on ferredoxins in cyanobacteria, the prokaryotes regarded as important producers of the oxygenic atmosphere and biomass for the food chain, as well as promising cell factories for biofuel production. Most studies of ferredoxins were performed in the model strain, Synechocystis P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
107
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(117 citation statements)
references
References 27 publications
2
107
0
Order By: Relevance
“…showed that slr0151 and slr0152 are transcribed separately from the upstream genes, possibly as bicistronic mRNA. Among other proteins, the slr0144–slr0152 gene cluster encodes the Slr0148 protein which has been recently annotated as ferredoxin 5 (Fd5) and shown to be a phosphoprotein, with modified T18 and T72 residues . Here, we demonstrate a relationship between phosphorylation of Fd5 and the SpkG kinase which was revealed by investigation of the Δslr0152(ΔspkG) mutant of Synechocystis 6803 with the targeted proteomic approach (the selected reaction monitoring, SRM).…”
mentioning
confidence: 81%
“…showed that slr0151 and slr0152 are transcribed separately from the upstream genes, possibly as bicistronic mRNA. Among other proteins, the slr0144–slr0152 gene cluster encodes the Slr0148 protein which has been recently annotated as ferredoxin 5 (Fd5) and shown to be a phosphoprotein, with modified T18 and T72 residues . Here, we demonstrate a relationship between phosphorylation of Fd5 and the SpkG kinase which was revealed by investigation of the Δslr0152(ΔspkG) mutant of Synechocystis 6803 with the targeted proteomic approach (the selected reaction monitoring, SRM).…”
mentioning
confidence: 81%
“…This permits the reduction of NADP + to NADPH (−320 mV) and allows them to act as a hub distributing electrons towards central metabolic reactions in plants and cyanobacteria [reviewed by (Hanke and Mulo 2013;Cassier-Chauvat and Chauvat 2014;Goss and Hanke 2014)]. Ferredoxin also plays a key role in cyclic electron transport, which balances the production of ATP and NADPH by recycling electrons through the plastoquinone pool and the cytochrome b 6 f complex (Yamori and Shikanai 2016).…”
Section: Characteristics Of Electron Carrier Proteins Involved In Phomentioning
confidence: 99%
“…Ferredoxin also plays a key role in cyclic electron transport, which balances the production of ATP and NADPH by recycling electrons through the plastoquinone pool and the cytochrome b 6 f complex (Yamori and Shikanai 2016). Photosynthetic organisms have several ferredoxin isoforms, with distinct roles (Hanke et al 2004;Cassier-Chauvat and Chauvat 2014). Their central role in distributing reducing power Arrows indicate linear electron transport during photosynthetic activity, starting with the oxidation of water and ending with the reduction of NADP + to NADPH.…”
Section: Characteristics Of Electron Carrier Proteins Involved In Phomentioning
confidence: 99%
See 1 more Smart Citation
“…The Prochlorococcus P-SSM2 phage Fd (pssm2-Fd) supports the reduction of phage phycoerythrobilin synthase (PebS), which catalyzes the reduction of biliverdin IXα to 3E/3Z phycoerythrobilin (27,28). While prior studies showed that some Fds support ET to diverse partner oxidoreductases (29)(30)(31)(32), it remains unclear how the biophysical properties of this and other phage Fds compare to host Fds, which can function as ET hubs that couple light harvesting to a range of reductive metabolic reactions (31)(32)(33). In addition, it is not known how the specific constraints of viral evolution might have modulated the primary structure and partner specificity of phage Fd.…”
Section: Introductionmentioning
confidence: 99%